İşlenmemiş PTFE ve Na-naftalenid sistemi ile yüzeyi modifiye edilmiş PTFE tozlarıyla doldurulmuş nanokompozitlerin DLP/LCD tipi 3D yazıcı kullanılarak üretilmesi - Çakır, Mustafa; Akın, Emre (İdris Karagöz, 2024)
Bu çalışma, modifiye edilmemiş PTFE ve Na-Naftalenid sistemi ile yüzeyi modifiye edilmiş PTFE tozları ile doldurulmuş DPGDA reaktif seyrelticili polyester akrilat reçinesinden oluşan DLP/LCD tipi 3D yazıcı ile yazılmış nanokompozitlerin mekanik özelliklerine odaklanmaktadır. Nanokompozitler her iki PTFE tozun %1 ila %6 arasında değişen yükleme oranlarında oluşturulmuştur. Na-Naftalen sistemi ile yapılan yüzey modifikasyon işleminden sonra yapılan X ışını foto elektron spektroskopisi verileri, OH, karbonil, C=C doymamış çift bağlar gibi fonksiyonel grupların PTFE tozlarının yüzeyinde bulunduğunu gösterdi. Çalışmada, DLP/LCD tipi 3D yazıcı ile elde edilen işlem görmemiş PTFE ve yüzeyi modifiye edilmiş PTFE tozları dolgulu nanokompozitlerin belirli bir orana kadar çekme dayanımı, Young modülü, Izod darbe dayanımı ve Shore D sertlik değerlerinde iyileşmeler olduğu ortaya konmuştur.

This study focuses on the mechanical properties of DLP/LCD-type 3D-printed nanocomposites comprised of polyester acrylate resin with DPGDA reactive diluent filled with untreated PTFE and surface-modified PTFE powders by the Na-Naphtalenide system. To obtain the nanocomposites, untreated and surface-modified PTFE powders were incorporated into the resin systems at loading ratios ranging from 1% to 6%. The X-ray photoelectron spectroscopy (XPS) data following the Na-naphthalene system treatment demonstrated the existence of functional groups such as OH, carbonyl, and C=C unsaturation groups on the surface of the untreated PTFE powders. The study showed improvements for the nanocomposites obtained through a DLP/LCD type 3D printer up to a certain ratio in terms of tensile strength, Young's modulus, Izod impact resistance, and Shore D hardness values. Evaluating the promising samples, the nanocomposites with surface-modified PTFE powders of 2% and 1% showed increases of 5.1% and 7.6% in ultimate tensile strength and Izod impact resistance compared to the unfilled polyester acrylate sample. On the other hand, the nanocomposite with untreated PTFE powders of 1% only showed increases of 2.4% and 3.2% in ultimate tensile strength and Izod impact resistance. Moreover, Young’s modulus showed less decrease for surface-modified PTFE-filled nanocomposites.
3D-printed nanocomposites filled with untreated and surface-modified PTFE powders treated by a Na-naphthalene-system
Keywords: Polymer Physics; Polimer Fiziği [EN] Polymer Technologies; Polimer Teknolojisi [EN] Polymers and Plastics; Polimerler ve Plastikler